2021
DOI: 10.1242/jeb.239798
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific variation in bristle number on forewings of tiny insects does not influence clap-and-fling aerodynamics

Abstract: Miniature insects must overcome significant viscous resistance in order to fly. They typically possess wings with long bristles on the fringes and use clap-and-fling mechanism to augment lift. These unique solutions to the extreme conditions of flight at tiny sizes (< 2 mm body length) suggest that natural selection has optimized wing design for better aerodynamic performance. However, species vary in wingspan, number of bristles (n), and bristle gap (G) to diameter (D) ratio (G/D). How this variation r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 94 publications
1
4
0
Order By: Relevance
“…After validating the simulations with experimental data, we leveraged the numerics to systematically explore the parameter space, including bristle length, diameter and number. Our main results, presented in figures 5 and 7, offer several insights that supplement prior research on bristled wing morphologies [35,44,47]. First, avoiding reconfiguration of the bristles during flight appears to be a general feature in the biological wings we examined (figure 5).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…After validating the simulations with experimental data, we leveraged the numerics to systematically explore the parameter space, including bristle length, diameter and number. Our main results, presented in figures 5 and 7, offer several insights that supplement prior research on bristled wing morphologies [35,44,47]. First, avoiding reconfiguration of the bristles during flight appears to be a general feature in the biological wings we examined (figure 5).…”
Section: Discussionsupporting
confidence: 80%
“…Drag and lift force production by bristled wings in linear and rotational translations and clap-and-fling movements have also been characterized [32,4044]. These studies confirmed that, at low Re , bristled wings enjoy aerodynamic advantages compared to their membraned counterparts because they experience only slightly decreased lift force while greatly reducing wing weight.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…In recent years, an increasing number of researchers have focused their attention on the smallest insects, with a special focus on their flying principles and aerodynamic mechanisms. According to the existing studies on insect morphology, unlike the larger insects with membranous wings, the smallest insects have distinctive bristled wings, e.g., thrips 4 , or partially bristled wings, e.g., the tiny wasp Encarsia Formosa 5,6 ; the specific morphology of the bristled wings can be found in the works of Huber and Noye 5 , Kolomenskiy et al 6 , Kasoju et al 7 and Zhao et al 8 .…”
mentioning
confidence: 99%